(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a strain of pathogenic bacteria that is a major problem in the world’s health. Due to their frequent interaction with humans, pets are one of the main risk factors for the spread of MRSA. The possibility for zoonotic transmission exists since frequently kept dogs and cats are prone to contract MRSA and act as reservoirs for spreading MRSA. The mouth, nose, and perineum are the primary locations of MRSA colonization, according to the findings of MRSA identification tests conducted on pets. The types of MRSA clones identified in cats and dogs correlated with MRSA clones infecting humans living in the same geographic area. A significant risk factor for the colonization or transmission of MRSA is human-pet contact. An essential step in preventing the spread of MRSA from humans to animals and from animals to humans is to keep hands, clothing, and floor surfaces clean. J. Adv. Vet. Anim. Res., 10(1): 1–13, March 2023 http://doi.org/10.5455/javar.2023.j641